Pengembangan Alat Peraga Valorem Fractus untuk Meningkatkan Pemahaman Konsep Siswa pada Materi Pecahan Senilai - Agrestian, Rizki; Nurhikmayati, Iik (Papanda Publisher, 2024)
This research aims to develop mathematical teaching aids based on development models with a focus on Equivalent Fractions material. MTs Nurul Hikmah Cigasong School is faced with limited resources and mathematics learning media, which results in low student interest and motivation to learn. Mathematics education in Indonesia still shows low quality compared to other countries. Therefore, this research was carried out to create the